EPO Signaling as a Predictive Marker of Disease Severity in RSV Infection - Shinagawa, Ayano; Toshio Kumai, Ko Sato, Anna S. Sedukhina, Kimino Minagawa, Hidekazu Yoshie, Tomoko Tsuruga, Keiko Oda,; Yamamoto, Hitoshi; Bernal, Juan A. (International Journal of Innovative Research in Medical Science, 2017)
Respiratory syncytial virus (RSV) infection is common in children and often causes severe respiratory clinical complications. Therefore, the establishment of biomarkers that predict severe clinical outcome is required. We performed in silico analysis across 2 datasets with available information on gene expression and disease severity to identify predictive factors of RSV infection progression. First, we selected differentially expressed genes (DEGs) in the severe group. Second, we added the DEGs in pathway analysis to observe an alteration of pathway status in the severe group. This analysis revealed candidate genes that affect pathway status. Finally, we calculated the odds ratio of the candidate genes involved in disease severity to a severe clinical course. We found that erythropoietin (EPO), a glycoprotein hormone controlled by hypoxia-inducible factor (HIF)-1, is upregulated in children with severe disease. Furthermore, increased expression of BNIP3L and FECH, downstream genes regulated by EPO levels, are highly associated with a severe course of the disease in both datasets. We propose that EPO-driven downstream signaling, especially increased expression of BNIP3L and FECH, is a biomarker that defines disease severity and potential clinical complications in children with RSV infection.